Examining The Influence of Moral Development and the Islamic Boarding School Setting on Student Morality in Bireuen District - Najmuddin; Muhammad Daniel; Muhammad Iqbal (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
Boarding schools were established in response to societal worries about the declining morality of youngsters influenced by their surroundings and social media. The new Islamic boarding school model provides dormitory-based education to cultivate excellent qualities. This concept aims to regulate moral development and provide rigorous instruction. Islamic boarding schools foster a conducive environment for students to develop morality through a variety of tactics and activities. This study examines the impact of moral education management and the environment in Islamic boarding schools on the moral character of students in Bireuen Regency. A quantitative method was applied, specifically through the use of surveys. The results demonstrate that both moral education management and the Islamic boarding school atmosphere significantly contribute to the development of students' morals. Data analysis reveals that these two factors collectively account for 52% of the variation in students' moral behavior, while the remaining 48% is likely influenced by other variables not included in this study. These findings suggest that structured moral guidance and a supportive boarding school environment play a key role in fostering students who are not only well-behaved but also responsible, disciplined, and capable of excelling academically and in extracurricular activities. The positive outcomes extend beyond individual students, offering broader benefits to the surrounding community and educational ecosystem.